Nutritional Status Among Students of a Private Medical College of Bangladesh - Akhter, Marufa; Biswas, Sailendra N; Ansari, MH (KYAMC Journal, 2017)
Nutritional status of Medical College students is an indicator of health & wellbeing at both the individual & the population level. This cross sectional study was carried out to assess the overweight and obesity as well as underweight among the students of Khwaja Yunus Ali Medical College, Enayetpur, Sirajgonj. All the students aged 18 -23 years reading in KYAMC were included in this study. Body weight, height and waist-hip ratio were measured and their relative information was collected with a self- administered, predesigned and pretested questionnaire. A total of 239 students data were found correct. Body mass index (BMI) was computed and categorized it into normal, overweight and obese according to WHO (1997) classification and analyzed for age, sex, waist-hip ratio and BMI category for assessing the nutritional status. In this study,157 (65.7%) students [male:53.5% & female:46.5%] were found in normal group, 38 students (15.9%) were overweight [male:44.7% and female:55.3%] and 44 students (18.4%) were in underweight group [male:50% and female:50%]. On splitting the data, the prevalence of underweight in different age groups decreases as the age advances but no such trend is observed in the case of overweight group and the proportion of overweight among the female students were more than that of male [18.1& vs 13.8%]. Waist-hip ratio was categorized into normal and overweight category and the prevalence of overweight is higher in female students than the male [80.8% vs 19.2%]. The results indicate the presence of a dual burden, underweight as well as overweight among the Medical College students in our country. Additional nutritional education, regular physical exercise and outdoor game facilities are recommended to overcome the problems. KYAMC Journal Vol. 6, No.-1, Jul 2015, Page 579-582